Greenhouse gas mitigation cost of energy from biogas : a techno-economic analysis of co-digestion of three types of waste in Cape Town - Malla, Lesego (Energy Research Centre, 2015)
This paper investigates, in the context of Cape Town the emission reduction potential (ERP) of energy from biogas and related cost. Two project-scale models and a city-scale model were developed. Substrates for project model 1 were organic fraction of municipal solid waste (OFMSW) and primary sludge (PS) from sewage works. Project model 2 considered waste paper sludge (WPS) and PS. For the city-scale model, substrates for project model 1 were extended to include total amounts of OFMSW and PS generated in Cape Town. Financial results show that at the REFIT tariff model 1 would have a higher internal rate of return (20.5%) than model 2 (5.6%). The landfill ERP of the project-scale models is 98 600 CO2 equivalent tons per year, corresponding to a weighted average capital investment of R372 per CO2 equivalent ton saved in year 1. The results for the city-scale model indicate that a landfill ERP of 458 000 CO2 equivalent tons per year can be expected at an investment cost of R287 per CO2 equivalent ton saved in year 1. Energy emissions from fossil fuels at city-scale are most effectively mitigated if coal rather than other fossil fuel based power and heat generation are replaced.